(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
This research aims at showing Nietzsche’s position on the Nihilism of his time, the Nihilism that represented the original event of Modernity in all its metaphysical connotations Our task in this research will be to reveal the mission of Nietzsche, whose efforts will be devoted to: making deep and profound changes based on his desire to conduct a cognitive critique of the higher values of Western civilization in all its philosophical, ethical, scientific and even political aspects, which led to the looting of existence and the fall of the human in the abyss of intellectual loss and also the obstruction of his ongoing process. Thus, the true attitude of Nietzsche and his urgent need for this critique had to be showed, and then to move forward to achieve perspective objectivity and justification for this critique in the research, last but not least illustrate deep humanity in Nietzsche’s philosophy which he tried hard to pursue.